Aplikasi Peta Interaktif 3D Pada Gedung Fakultas Teknik Universitas Lampung - Aristoteles Aristoteles; Dinda Fitrialoka; Yohana Tri Utami (Institut Bakti Nusantara, 2023)
The advancement of technology allows for various developments, such as the creation of systems and applications that facilitate human tasks and transactions. However, the existence of applications also requires research to measure user satisfaction, one of which is the DANA application. DANA is a smart application that provides convenience in transactions. With DANA, people can easily make online and offline payments using electronic money. This research aims to determine the level of user satisfaction with the DANA application using the End User Computing Satisfaction (EUCS) method. This method focuses on user satisfaction by analyzing the application based on content, accuracy, format, user-friendliness, and timeliness. The research conducted is descriptive research using a questionnaire as the research instrument. The sampling technique used in this study is random sampling. This research is deemed necessary to determine the level of user satisfaction. Furthermore, the data is processed using SPSS Version 25. The results show that the level of user satisfaction for the five variables is as follows: the Content variable received a high satisfaction score with a percentage value of 78.8%, the Accuracy variable received a high satisfaction score with a percentage value of 78.7%, the Format variable received a high satisfaction score with a percentage value of 79.2%, the Ease of Use variable received a high satisfaction score with a percentage value of 79.2%, and the Timeliness variable received a high satisfaction score with a percentage value of 77.3%.